Modelos Polinomiais para Detecção de Efeito Anódico - Amate, Jorge Farid (2009)
In industrial processes, where parameters estimation and standard recognition are desired, digital filters technology is used to do estimation. The digital filter is responsible for prediction and filtering process. Then, the filter behavior can be analyzed based on performance, gains and others variables linked to the specified model. However, to obtain trusty variables and data to estimate the process in question, a model that represents well the physics plant is needed. To do this, are applied techniques based on Systems Identification where we obtain the ARX, ARMAX, Output-Error and Box-Jenkins models of the electrolytic pot. Results, validation and their analysis, applied in standard recognition, using different structures are presented.